Soil quality and soil fertility status in major soil groups at the Tombel area, South-West Cameroon - Nguemezi, C.; Tematio, P.; Yemefack, Martin; Tsozue, D.; Silatsa, T.B.F. (Elsevier, 2020)
Among the greatest challenges of Sub-Saharan Africa is the need for more crop production for supplying the increasing demand of its growing population. For this purpose, knowledge on soil resources and their agricultural potentials is important for defining proper and appropriate land use and management. We thus investigated on the status of soil fertility in Tombel area, in order to produce such knowledge through understanding and monitoring the impact of physicochemical properties of soil. Diverse analyses performed on various datasets demonstrated the direct impact of physicochemical properties of soil and derived soil fertility parameters on major constraints for plant growth and optimal crop production such as water retention capacity, roots development, soils aeration, nutrients availability, nutrients abundance and cations balance. Based on physicochemical soil properties, fertility parameters and Soil Quality Index (SQI), four soil fertility classes were identified in the area: (i) very good fertility soils (66 km2) that corresponds to Dystric Vitric Andosols (Melanic) above 500m asl; (ii) good fertility soils (506 km2), grouping Dystric Vitric Andosols (Melanic) below 500m asl and Leptic Fragic Umbrisols; (iii) fairly good fertile soils (787 km2) including Dystric Fragic Cambisols (Humic), Rhodic Acrisols (Cutanic Humic), Fragic Umbrisols (Arenic), and Mollic Ferralsols (Eutric Humic); (iv) poorly fertile soils (375 km2) including Umbric Andosols (Fragic) and Umbric Pisoplinthic Plinthosols (Haplic Dystric). The principal indicators controlling soil quality in the Tombel area as derived from ANOVA and PCA analyses, are: Ca, Mg, pH water, organic matter (OM), available P, total Nitrogen and CEC. Four of the seven indicators (Ca, pH, OM, P) were also identified as important indicators for assessing the fertility status of the different soils groups in the Tombel area.